2012
DOI: 10.2147/ijn.s34663
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotubes promote rat vascular adventitial fibroblasts to transform into myofibroblasts by SM22-α expression

Abstract: Abstract:The aim of this study was to explore whether single-wall carbon nanotubes (SWCNTs) can be used as artery tissue-engineering materials by promoting vascular adventitial fibroblasts (VAFs) to transform into myofibroblasts (MFs) and to find the signal pathway involved in this process. VAFs were primary cultured and incubated with various doses of SWCNTs suspension (0, 0.8, 3.2, 12.5, 50, and 200 µg/mL). In the present study, we used three methods (MTT, WST-1, and WST-8) at the same time to detect the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…SWCNTs induced TGF-β1 expression and promoted rat vascular adventitial fibroblasts to transform to myofibroblasts, indicated by the gained expression of SM22-α (smooth muscle protein 22-α), which is a smooth muscle cell-specific protein and a marker of myofibroblast differentiation [117]. SWCNTs induced TGF-β1 secretion and activation in a dose-dependent manner in human lung fibroblasts (CRL-1490) [118].…”
Section: Tgf-β1mentioning
confidence: 99%
See 1 more Smart Citation
“…SWCNTs induced TGF-β1 expression and promoted rat vascular adventitial fibroblasts to transform to myofibroblasts, indicated by the gained expression of SM22-α (smooth muscle protein 22-α), which is a smooth muscle cell-specific protein and a marker of myofibroblast differentiation [117]. SWCNTs induced TGF-β1 secretion and activation in a dose-dependent manner in human lung fibroblasts (CRL-1490) [118].…”
Section: Tgf-β1mentioning
confidence: 99%
“…Alternatively, CNT fibers may directly interact with cell surface receptors, such as the pattern recognition receptors. SWCNTs have been observed inside rat vascular adventitial fibroblasts after exposure for 24 and 48 h [117]. MWCNTs were found to be accumulated on the surface of NIH 3T3 fibroblasts 3 h post-exposure, and some MWCNTs entered the cell by way of endocytosis 24 h post-exposure [98].…”
Section: Role Of Tissue Stiffness Mechanical Force and Receptorsmentioning
confidence: 99%
“…In 2006, Garibaldi and colleagues exposed cardiac muscle cells from the H9c2 (2-1) heart cell line to pure single-walled nanotubes suspended in culture medium, and observed no short-term toxicity of soluble CNTs (limited proliferative ability and morphological changes were identified only after CNTs-treated cells reseeding; Garibaldi et al, 2006). Recently, Lin et al (2012) reported that dispersed suspension of pure single-walled CNTs in the culture medium promotes vascular adventitial fibroblasts transformation into myofibroblasts, with an up-regulation of the SM 22−α differentiation marker expression, although accompanied by an increased oxydative damage (Lin et al, 2012). It has to be noted, however, that pure (non-functionalized) CNTs are a water-insoluble, aggregate-forming material, and the presence of CNTs aggregates is related to decreased cell viability, at least for smooth muscle cells (Raja et al, 2007).…”
Section: Impact Of Cnts Scaffolds On Myocytes Morphology Proliferatimentioning
confidence: 99%
“…Lin and colleagues [64] studied in vitro how pristine SWCNTs dispersed in an extracellular medium can affect the viability of vascular adventitial fibroblasts and their transformation into myofibroblasts. Their results showed an up-regulated expression of a specific differentiation marker, accompanied, however, by an increased generation of the most biologically significant free radicals, the reactive oxygen species (ROS).…”
Section: Reviewmentioning
confidence: 99%